2020
DOI: 10.1080/1331677x.2020.1825105
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Confucian culture on corporate tax avoidance: evidence from China

Abstract: This study investigates whether Confucian culture can influence corporate tax avoidance. We measure Confucianism using geographical-proximity based method and opt ordinary least square regression considering a sample of Chinese firms during 2004-2016. We find strong evidence that Confucian culture and tax avoidance are negatively associated and this association is less prominent for state-owned firms. Additional analysis shows that tax enforcement efforts mitigate the effect of Confucianism on tax avoidance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…Corporate tax evasion and Confucian culture have a negative relationship. Confucian culture discourages corporate tax evasion behavior (Chen, Xu, & Jebran, 2021). Research on how culture affects the explanations for tax cheating in various nations reveals that masculinity and the avoidance of uncertainty reduce the rationale for tax cheating, while individualism and power distance boost the justification (Bani-Mustafa, Al Qudah, Damrah, & Alameen, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Corporate tax evasion and Confucian culture have a negative relationship. Confucian culture discourages corporate tax evasion behavior (Chen, Xu, & Jebran, 2021). Research on how culture affects the explanations for tax cheating in various nations reveals that masculinity and the avoidance of uncertainty reduce the rationale for tax cheating, while individualism and power distance boost the justification (Bani-Mustafa, Al Qudah, Damrah, & Alameen, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Beberapa variabel umum yang banyak digunakan sebagai determinan penghindaran pajak antara lain thin capitalization, hubungan istimewa, aktivitas luar negeri atau multinationality, manajemen laba dan siklus bisnis atau karakteristik bisnis (Falbo & Firmansyah, 2018;Aryotama & Firmansyah, 2020a;Falbo & Firmansyah, 2021;Ferdiawan & Firmansyah, 2017;Dwi Laksono & Firmansyah, 2020;Aryotama & Firmansyah, 2020b;Nurhandono & Firmansyah, 2017;Irawan, 2020;Utami & Irawan, 2022;Wijaya & Rahayu, 2021;Hidayat & Wijaya, 2021;Wijaya & Setiawan, 2021). Beberapa studi lain menggunakan variabel di luar komponen laporan keuangan sebagai determinan penghindaran seperti ditunjukkan oleh (Chen et al, 2021;Ferdiawan & Firmansyah, 2017;Finér & Ylönen, 2017;Hasan et al, 2021;Hasseldine & Morris, 2013).…”
Section: Kajian Pustakaunclassified
“…Guided by the ideas of "three principles and five rules" and "unity of righteousness and profit," Confucian culture can significantly reduce agency problems in modern firms (Chen et al, 2019) by restraining the self-interested behavior of insiders (Du, 2015), and influence surplus management behavior (Schmitz et al, 2019), enhance technological innovation (Yan et al, 2021), and thus promote firm growth. It has also been demonstrated that Confucian culture can effectively reduce firm tax avoidance (Chen et al, 2021) To enrich the extant research, this paper examines the influence of Confucian culture on environmental information disclosure. Furthermore, Taoist culture, like Confucian culture , has also continued in China for thousands of years and is an important part of Chinese culture.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that firms' employee hiring (Chen et al, 2014; Chen, Lim, et al, 2020), taking social responsibility (Xiu et al, 2022), tax avoidance behavior (Chen et al, 2021), and cash holdings (Chen, Ye, et al, 2020) are significantly influenced by Confucian culture. Guided by the ideas of “three principles and five rules” and “unity of righteousness and profit,” Confucian culture can significantly reduce agency problems in modern firms (Chen et al, 2019) by restraining the self‐interested behavior of insiders (Du, 2015), and influence surplus management behavior (Schmitz et al, 2019), enhance technological innovation (Yan et al, 2021), and thus promote firm growth.…”
Section: Introductionmentioning
confidence: 99%